Benefits of Judo Practice for Individuals with Neurodevelopmental Disorders: A Systematic Literature Review - Gaston Descamps; Maria João Campos; Terry Rizzo; Viktorija Pečnikar Oblak; Alain Guy Massart (MDPI AG, 2024)
This systematic literature review evaluates the benefits of judo practice designed for individuals with neurodevelopmental disorders (NDDs), including autism spectrum disorder (ASD), Intellectual Developmental Disorders (IDDs), and attention-deficit/hyperactivity disorder (ADHD). This review adheres to the PRISMA 2020 guidelines, focusing on the physical, social, emotional, and cognitive benefits of judo. A comprehensive search across databases, such as PubMed, Google Scholar, ResearchGate, B-On, and Scopus, was conducted, and relevant studies were selected based on explicit inclusion and exclusion criteria. Sixteen intervention studies were included, which contributed to a detailed understanding of the impact of judo. The results indicated significant benefits in terms of physical activity, social interactions, emotional well-being, and cognitive functions among participants. A synthesis of results is presented, showing the overall positive effect of judo practice. This review highlights the potential of judo as supportive therapy for individuals with NDDs, advocating its inclusion in therapeutic and educational settings. Limitations due to study heterogeneity and the need for more randomized controlled trials are also discussed.